ЯЗЫКОВАЯ РЕПРЕЗЕНТАЦИЯ ОППОЗИЦИИ «ВЗРОСЛЫЕ – ДЕТИ» В ТВОРЧЕСТВЕ ЖАКА ПРЕВЕРА - Кулагина, Ольга (Conversatoria Litteraria, 2020)
This paper deals with linguistic representation of relationship between adults and children in Jacques Prévert’s oeuvre. The texts under analysis are poems from seven collections published at different periods. Various ways of transmissing the conflict between childhood and maturity, which is also the one between youth and old age, are examined in the paper.